2002
DOI: 10.1161/01.cir.0000023041.26199.29
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemic Stenosis Resistance Index for Evaluation of Functional Coronary Lesion Severity

Abstract: Background-Both coronary blood flow velocity reserve (CFVR) and myocardial fractional flow reserve (FFR) are used to evaluate the hemodynamic severity of coronary lesions. However, discordant results between CFVR and FFR have been observed in 25% to 30% of intermediate coronary lesions. An index of stenosis resistance based on a combination of intracoronary pressure and flow velocity may improve the assessment of functional coronary lesion severity. Methods and Results-Single photon emission computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 34 publications
2
113
0
1
Order By: Relevance
“…33 HMR represents the mean distal coronary pressure to mean distal flow velocity ratio during maximal hyperemia, 34 whereas HSR is defined as the ratio between the pressure drop across the stenosis and distal peak flow velocity during maximal hyperemia (Figure 2). 35 Of note, in 1 study, HSR was a more powerful predictor of reversible perfusion defects as compared with FFR or CFVR. 35 Furthermore, a recent study by van de Hoef et al 36 provided important insights into the role of HMR in the identification of ischemiainducing coronary stenoses by FFR.…”
Section: Niccoli G Et Almentioning
confidence: 87%
See 2 more Smart Citations
“…33 HMR represents the mean distal coronary pressure to mean distal flow velocity ratio during maximal hyperemia, 34 whereas HSR is defined as the ratio between the pressure drop across the stenosis and distal peak flow velocity during maximal hyperemia (Figure 2). 35 Of note, in 1 study, HSR was a more powerful predictor of reversible perfusion defects as compared with FFR or CFVR. 35 Furthermore, a recent study by van de Hoef et al 36 provided important insights into the role of HMR in the identification of ischemiainducing coronary stenoses by FFR.…”
Section: Niccoli G Et Almentioning
confidence: 87%
“…35 Of note, in 1 study, HSR was a more powerful predictor of reversible perfusion defects as compared with FFR or CFVR. 35 Furthermore, a recent study by van de Hoef et al 36 provided important insights into the role of HMR in the identification of ischemiainducing coronary stenoses by FFR. They observed that the diagnostic accuracy for inducible ischemia on myocardial perfusion scans of a positive compared with a negative FFR was significantly higher only in the presence of a high HMR (at the 0.75 and 0.80 FFR cutoff).…”
Section: Niccoli G Et Almentioning
confidence: 87%
See 1 more Smart Citation
“…Minimal MVR therefore excludes systolic compressive resistance and better informs vascular resistance, and has been shown not to be influenced by coronary artery stenosis severity 18. Trans‐stenotic pressure gradient (aortic pressure (P a )−P d ), P d /P a ratio, and epicardial stenosis resistance (P a −P d /average peak velocity)19 were also calculated as measures of stenosis severity. Epicardial stenosis resistance, defined as the ratio of the pressure drop across the stenosis to distal coronary flow velocity, normalizes the pressure drop for the magnitude of epicardial coronary flow velocity at which it was obtained, providing a more objective assessment of hemodynamic stenosis severity.…”
Section: Methodsmentioning
confidence: 99%
“…Both the hyperaemic stenosis resistance (HSR) and dp v50 , which is derived from the diastolic flow velocity-pressure gradient (v-dp) relation, have been found to determine the haemodynamic significance of a coronary stenosis with a high accuracy. [3][4][5][6] Patients frequently have multiple stenoses in the same coronary artery. Compared with a single stenosis, multiple consecutive stenoses result in a greater reduction in maximal flow.…”
mentioning
confidence: 99%